Orbital Fractures in Childhood - Valente, Luisa (Ann Maxillofac Surg, 2019)
Pediatric orbital floor fractures exhibit distinctive features that distinguish them from orbital injuries seen in the adult population. This is mainly due to different anatomy and mechanical properties of the orbital bones in children. The management of pediatric orbital floor fractures requires consideration of these factors, including the age of the patient and therefore child's growth potential, using, if possible, a minimally invasive surgical approach. The aim of this paper is to report a case of a 1-year-old male child with a surgically treated blowout fracture of the orbital floor. To enable early diagnosis and treatment, accurate physical examination is mandatory, but a computed tomographic examination is important, especially in younger patients because of their inability to fully express their symptoms and poor compliance. We discuss the specific presentation and diagnostics of orbital floor fractures in early childhood and the related surgical planning and treatment.